+0  
 
0
368
2
avatar+280 

Thanks in dac

Veteran  May 25, 2017
 #1
avatar
0

Possible derivation:
d/dx(tan^(-1)(sin(5 x)))
Using the chain rule, d/dx(tan^(-1)(sin(5 x))) = ( dtan^(-1)(u))/( du) ( du)/( dx), where u = sin(5 x) and ( d)/( du)(tan^(-1)(u)) = 1/(1 + u^2):
 = (d/dx(sin(5 x)))/(1 + sin^2(5 x))
Using the chain rule, d/dx(sin(5 x)) = ( dsin(u))/( du) ( du)/( dx), where u = 5 x and ( d)/( du)(sin(u)) = cos(u):
 = cos(5 x) d/dx(5 x)/(1 + sin(5 x)^2)
Factor out constants:
 = (5 d/dx(x) cos(5 x))/(1 + sin^2(5 x))
The derivative of x is 1:
Answer: | = (15 cos(5x)) / (1 + sin^2(5x))

Guest May 25, 2017
 #2
avatar+90055 
+1

 

 

Note  .......derivative of arctan (u)  =   1 / ( 1 + u^2) * du  .....so......

 

f(x)  =   arctan (sin (5x))   =   [  1 /  [ 1 + (sin(5x) )^2]  * 5 cos (5x)  =

 

[ 5 cos (5x) ]  /  [ 1 + sin2(5x) ]

 

 

cool cool cool

CPhill  May 25, 2017

35 Online Users

avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.